PROFESSIONAL MOBILITY AS A FACTOR OF BORDER GUARDS READINESS FOR PROFESSIONAL ACTIVITY: UKRAINIAN AND EUROPEAN EXPERIENCE - Ісламова, О. (Київський національний університет імені Тараса Шевченка, 2021)
The article presents an analysis and generalization of approaches to the nature and content of professional mobility. It is concluded that professional mobility is directly interrelated with readiness to work in the specialty, since these two concepts have common elements in the structure, in particular professional knowledge, abilities, skills and professionally important qualities. Taking into account the results of the analysis of research related to the problem of professional mobility, it was found out that this concept can be defined as readiness and ability to work in the context of transformation of professional (production, service) tasks, development of new specialties or changing them. Professional mobility covers the ability to successfully switch to another activity or change types of activities, effectively use the system of generalized professional techniques to perform any tasks in the professional sphere, and it is relatively easy to move from one type of activity to another. For professional mobility, it is important to have a high level of generalized professional knowledge, experience in improving them and obtaining them independently. The results of the review of publications on the research topic suggest that there are two types of mobility – horizontal and vertical. Horizontal mobility involves the transition of an individual or social object from one social position to another, which is at the same level, as well as a change of place of residence. As for vertical mobility, it involves the transition of an individual or social object from one social position to another. It was found out that mobility is an integrative property that is formed and developed during practical, educational, social, socio-cultural activities of a person and provides him with the opportunity to realize his inclinations, abilities, opportunities. It was found that in the context of training of border guard agencies' personnel in the EU, professional mobility of border guards is ensured by their high level of interoperability, which is a necessary condition for effective organization of protection of EU external borders by representatives of various European border guard agencies. The most common form of ensuring the professional mobility of European border guards is working within the Permanent Corps of the European Border and Coast Guard Agency Frontex. The training of Ukrainian Border Guard Agency's staff in the context of European integration requires the study of the experience of border agencies in EU countries to provide conditions for the development of professional mobility of border guards, which requires further thorough study of the outlined topic.

Представлено узагальнення вітчизняного та європейського досвіду щодо сутнісно-понятійних уявлень про професійну мобільність як чинник готовності прикордонників до діяльності за фахом. Зроблено висновок про те, що професійна мобільність безпосередньо взаємопов'язана з готовністю до діяльності за фахом, оскільки ці два поняття мають у структурі спільні елементи, зокрема, професійні знання, уміння, навички та професійно-важливі якості. З урахуванням результатів аналізу досліджень, пов'язаних з проблемою професійної мобільності, з'ясовано, що це поняття можна визначити як готовність і здатність до діяльності в умовах трансформації професійних (виробничих, службових) завдань, освоєння нових спеціальностей або змін у них. Професійна мобільність охоплює здатність успішно переключатися на іншу діяльність або змінювати види діяльності, ефективно використовувати систему узагальнених професійних прийомів для виконання будь-яких завдань у професійній сфері, порівняно легко переходити від одного виду діяльності до іншого. Мобільність визначено інтегративною властивістю, що формується і розвивається під час практичної, освітньої, соціальної, соціокультурної діяльності людини та надає їй можливість реалізувати свої задатки, здібності, схильності, можливості. З'ясовано, що в контексті підготовки персоналу прикордонних відомств у країнах ЄС професійна мобільність прикордонників забезпечується їхнім високим рівнем інтероперабельності, що є необхідною умовою для ефективної організації охорони зовнішніх кордонів ЄС представниками різних європейських прикордонних відомств. Найпоширенішою формою забезпечення професійної мобільності європейських прикордонників є робота в межах Постійного корпусу європейської агенції прикордонної і берегової охорони Фронтекс. Підготовка персоналу ДПСУ за умов євроінтеграції потребує вивчення досвіду прикордонних відомств країн ЄС щодо забезпечення умов для розвитку професійної мобільності прикордонників, що вимагає подальшого ґрунтовного дослідження окресленого напряму.
ПРОФЕСІЙНА МОБІЛЬНІСТЬ ЯК ЧИННИК ГОТОВНОСТІ ПРИКОРДОННИКІВ ДО ДІЯЛЬНОСТІ ЗА ФАХОМ: ВІТЧИЗНЯНИЙ ТА ЄВРОПЕЙСЬКИЙ ДОСВІД
Keywords: professional mobility; border guards; professional activity; professional training; social mobility; professional career; професійна мобільність; прикордонники; професійна діяльність; професійна підготовка; соціальна мобільність; професійна кар'єра